In vivo EROD assays with the zebrafish (Danio rerio) as rapid screening tools for the detection of dioxin-like activity - Kais, Britta; Braunbeck, Thomas (The science of the total environment, 2017)
The present study compares two alternative in vivo approaches for the measurement of ethoxyresorufin-O-deethylase (EROD) activity in zebrafish (Danio rerio) following exposure to acetonic model sediment extracts: (1) the live-imaging EROD assay for the direct detection of EROD induction in individual livers via epifluorescence, and (2) the fish embryo EROD assay in subcellular fractions derived from entire zebrafish embryos after in vivo exposure. For toxicity assessment, each sediment extract was tested with the standard fish embryo test (FET). Upon completion of a functioning liver after 72h, the embryos gave a distinct fluorescent signal in the liver, and a corresponding EROD activity could be detected in the fish embryo EROD assay. The exposure time in the live-imaging EROD assay was reduced to 3h, which resulted in a stronger, less variable and more sensitive EROD response. Overall, the live-imaging and the fish embryo EROD assays showed the same tendencies and gave comparable results, e.g. a concentration-dependent increase in EROD activity at concentrations one order of magnitude below concentrations producing macroscopically visible abnormalities. At higher concentrations, however, a decrease of EROD activity was observed in either test. Both tests ranked the three model sediment extracts in the same order. Results indicate that both test systems complement each other and together provide a rapid and reliable in vivo tool to investigate the presence of dioxin-like substances in environmental samples.